The Moderate Patterns of Islamization in Java Under Political Fluctuations in Early 20th Century - Wahyudhi, Nostalgiawan (International Journal of Nusantara Islam, 2015)
The previous studies of islamization in Java follow a clear distinction of priyayi-abangan-santri thesis, which was in its development gradually incompatible to capture the changing of political preferences of Javanese Muslims. This paper examines what kind of patterns formed on the dynamics of the process of Islamization in Java under the influence of socio-political changes. The output of this paper perhaps shows the pattern of islamization in Java under the dynamic changes of Indonesian politics in the early twentieth century. The pattern of islamization in Java was influenced, firstly, by ethical policy, secondly, the transmission of Middle East Islam, and, thirdly, politization of Islam by colonial government. The ethical policy encouraged the creation of a public space for political contestations that determined the new identity of Indonesian elite. The transmission of Middle Eastern Islam triggered the polarization of Javanese Muslims into two patterns: the modernist Muslim strengthened the pattern of priyayi-santri in urban communities with Islamization through modern institutions. The traditionalist Muslim developed an intellectual genealogy through pesantren networks scattered in the rural areas created the pattern of santriabangan. Meanwhile the politization of Islam by colonial government created a benefit to the unification of Islamic institutions.